EXPLORING JULIA AGUSTINE’S RESPONSES TO OVERCOME RACISM IN ALICE CHILDRESS’ WEDDING BAND: A LOVE/HATE STORY IN BLACK AND WHITE - Lengari, Yoana Gita Pradnya; Dewi, Monica Anggraeni (English Literature Department, Faculty of Economics, Law, and Humanities, 2024)
This research explores the portrayal of racial discrimination in Alice Childress’ 1962 play, “Wedding Band: A Love/Hate Story in Black and White.” The story takes place in the segregated South Carolina in the World War I. This research utilizes the sociocultural-historical approach by examining the ways Julia Agustine, the main character of the play, experiences and responds to racial discrimination. The analysis identifies specific racial discrimination Julia faces. The racial discrimination Julia faces can be seen in the form of racial prejudice in the form of refusal of physical contact and helpful gestures based on racial stereotypes; unwanted sexual harassment from a white male character; and the prohibition of interracial marriage with her white boyfriend Herman. Furthermore, the study examines Julia’s responses to these challenges. Drawing on her qualities of courage, faith, perseverance, and intelligence, Julia shows resistance through anger, confrontation, and refusal of those who mistreat her. By analyzing Julia’s journey, this study aims to contribute to a deeper understanding of the complex nature of racial discrimination and the resilience required to navigate through it.